2019
DOI: 10.1021/acs.energyfuels.9b03332
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Stability, Physical Properties, and Electrostatic Breakup of Surfactant-Loaded Aluminum/n-Decane Nanofluid Fuel: Nanoparticle Size Effect

Abstract: The n-decane fuel/n-decane-based nanofluid fuel could be one of the most promising alternative fuels as aviation kerosene for aerospace application. This paper proposes Al/n-decane nanofluid fuel with the surfactant of sorbitan monooleate (SP-80) and investigates the size effect of Al nanoparticle (SA, 56.0 nm; SB, 74.4 nm,; SC, 93.4 nm) on its dispersion stability, physical properties, and electrostatic breakup performance. Dynamic light scattering (DLS) measurements and numerical calculations of particle col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 72 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…In addition, water injection in coal seams lasts for the long term. Therefore, as time goes on, NPs may aggregate and sediment, which substantially reduces the advantageous performance of nanofluids and causes tremendous trouble to engineering applications. , Li et al studied the influences of metallic aluminum NPs on the stability of nanofluid fuels and revealed that the size of NPs seriously influences the stability and physical properties of the dispersion system of nanofluids. Nithiyanantham et al studied the influences of the particle size of SiO 2 NPs on the stability of molten salt-based nanofluids and found that such nanofluids prepared with SiO 2 NPs of 27–450 nm exhibit good geothermal physical properties and stability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, water injection in coal seams lasts for the long term. Therefore, as time goes on, NPs may aggregate and sediment, which substantially reduces the advantageous performance of nanofluids and causes tremendous trouble to engineering applications. , Li et al studied the influences of metallic aluminum NPs on the stability of nanofluid fuels and revealed that the size of NPs seriously influences the stability and physical properties of the dispersion system of nanofluids. Nithiyanantham et al studied the influences of the particle size of SiO 2 NPs on the stability of molten salt-based nanofluids and found that such nanofluids prepared with SiO 2 NPs of 27–450 nm exhibit good geothermal physical properties and stability.…”
Section: Introductionmentioning
confidence: 99%